Wakefield excitation in plasma by ramped sequence of ramped electron bunches - Maslov, V.I.; Onishchenko, I.N.; Yarovaya, I.P. (Вопросы атомной науки и техники, 2012)
It has been shown that wakefield in the regions, occupied by bunches-drivers, does not depend on a longitudinal coordinate for certain lengths of bunches, distance between bunches and the charge is ramped by linear law. For increase of number of accelerated electrons long sequence of electron bunches-drivers, charge of which is distributed according to linear law along each bunch, providing large transformation ratio and homogeneous wakefield, which enable to completely decelerate bunches-drivers, has been constructed. Показано, что кильватерное поле в областях локализации сгустков-драйверов не зависит от продольной координаты при определенных длинах сгустков и промежутках между ними, если заряд профилирован по линейному закону. Для увеличения числа ускоренных электронов построена длинная последовательность электронных сгустков-драйверов, заряд у которых распределен по линейному закону вдоль каждого сгустка, обеспечивающая большой коэффициент трансформации и однородное кильватерное поле, которое позволяет полностью затормозить сгустки-драйверы. Показано, що кільватерне поле в межах локалізації згустків-драйверів не залежить від поздовжньої координати при відповідних довжинах згустів та проміжках між ними, якщо заряд профільован відповідно лінійному закону. Для збільшення числа прискорених електронів побудована довга послідовність електронних згустів-драйверів, заряд в яких розподілений по лінійному закону вздовж кожного згустку, яка забезпечує значний коефіцієнт трансформації та однорідне кільватерне поле, яке дозволяє повністю загальмувати згустки-драйвери.